Native American legends [videorecording (DVD)]. (A&E Home Video, 2008)
They fought hard to protect the lands where they had lived and thrived since time immemorial. Thrill to these larger-than-life, legendary men whose very names conjure brave and ferocious warriors whose unrelenting stamina and indomitable spirit continue to inspire and awe throughout the ages. Learn of their exploits, strategies and stunning victories at the Battle of Little Big Horn and other legendary conflicts of the old west.